1989
DOI: 10.1007/bf00261172
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a gene conferring resistance to zinc and cadmium ions in the yeast Saccharomyces cerevisiae

Abstract: A DNA fragment conferring resistance to zinc and cadmium ions in the yeast Saccharomyces cerevisiae was isolated from a library of yeast genomic DNA. Its nucleotide sequence revealed the presence of a single open reading frame (ORF; 1326 bp) having the potential to encode a protein of 442 amino acid residues (molecular mass of 48.3 kDa). A frameshift mutation introduced within the ORF abolished resistance to heavy metal ions, indicating the ORF is required for resistance. Therefore, we termed it the ZRC1 (zinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
124
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(127 citation statements)
references
References 51 publications
3
124
0
Order By: Relevance
“…While the zinc responsiveness of these genes may be caused by indirect effects of zinc status, it is exciting to speculate that Zap1p plays a global role in the regulation of zinc homeostasis and the metabolic response to zinc limitation. Zinc-responsive transcription of ZRC1 is particularly intriguing because this gene encodes a protein thought to transport zinc from the cytoplasm into an unknown organelle (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the zinc responsiveness of these genes may be caused by indirect effects of zinc status, it is exciting to speculate that Zap1p plays a global role in the regulation of zinc homeostasis and the metabolic response to zinc limitation. Zinc-responsive transcription of ZRC1 is particularly intriguing because this gene encodes a protein thought to transport zinc from the cytoplasm into an unknown organelle (20).…”
Section: Discussionmentioning
confidence: 99%
“…The delicate balance of intracellular zinc is accomplished through precise homeostatic regulation mediated by a number of mechanisms. These include binding of the metal by cytoplasmic macromolecules such as metallothioneins (14) and phytochelatins (27), zinc storage in intracellular compartments (3,20,25), and transport of the metal out of the cell (26).…”
mentioning
confidence: 99%
“…All these three peptides also contained three additional cysteine motifs -C(x) 4 C, C(x) 3-5 CC, CC -and a His rich domain within their extended C-terminus which could be involved in heavy metal binding. Further examination of the two putative HMA4 COOH tails revealed that the C(x) 3 CC motifs were in a larger cysteine motif, C(x) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] C(x) 3 CC for Thlaspi and C(x) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] C(x) 3 CC for Arabidopsis. This sequence is similar to the recently described TRASH domain, C(x) [19][20][21][22] C(x) 3 C, predicted to be involved in heavy metal sensing, trafficking and resistance [25].…”
Section: Isolation Of T Caerulescens Hma4 Cdnamentioning
confidence: 99%
“…A key feature of the ZIP family is that these proteins transport zinc and/or other metal ions from the extracellular space (or organellar lumen) into the cytosol ( Eide, 2006). CDF transporters were first described in S. cerevisiae (Zrc1p) ( Kamizono et al, 1989) and in the Gram-negative bacteria Ralstonia metallidurans (CzcD) ( Nies, 1992), but they were later also found in plants and animals (see in Montanini et al, 2007). The key feature of the CDF transporters is that they export zinc and/or other metal ions out of the cells, or they sequester them into intracellular compartments ( Eide, 2006and Peiter et al, 2007, thus reducing cytosolic metal concentrations ( Anton et al, 1999 andMacDiarmid et al, 2002).…”
Section: Introductionmentioning
confidence: 99%